2022
DOI: 10.3390/ijerph19020962
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Toxicity of Bisphenol A in Reproduction and Its Effect on Fertility and Embryonic Development in the Zebrafish (Danio rerio)

Abstract: Bisphenol A (BPA) is a chemical substance commonly used in the manufacture of plastic products. Its inhalation or ingestion from particles in suspension, water, and/or polluted foods can trigger toxic effects related to endocrine disruption, resulting in hormonal, reproduction, and immunological alterations in humans and animals. The zebrafish (Danio rerio) is an ideal experimental model frequently used in toxicity studies. In order to assess the toxic effects of BPA on reproduction and embryonic development i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Thus, they have their greatest impact on reproduction not only in humans but also in birds, animals and fish (Patisaul, 2021;Robaire et al, 2022). More recent reports confirm these observations and clinical cases are becoming more evident (Rahman et al, 2018;You and Song, 2021;Reis et al, 2022).…”
Section: Environmental Pollution and Endocrine Disruptorsmentioning
confidence: 90%
“…Thus, they have their greatest impact on reproduction not only in humans but also in birds, animals and fish (Patisaul, 2021;Robaire et al, 2022). More recent reports confirm these observations and clinical cases are becoming more evident (Rahman et al, 2018;You and Song, 2021;Reis et al, 2022).…”
Section: Environmental Pollution and Endocrine Disruptorsmentioning
confidence: 90%
“…In recent years, increasing evidence points to BPA and its analogs as endocrine disrupting compounds that may inhibit biosynthesis, thereby affecting the male gonad development and maturation and eventually leading to TDS. 2,4,27 This research aimed to explore the effect of TMBPA (a BPA analog) on FLC function. We gavaged pregnant female rats with TMBPA from GD 14 to GD 21 and found that TMBPA promoted the proliferation of differentiating FLCs and putative stem cells possibly through activating ESR1, thereby activating the AKT1/AKT2 pathway and further increasing cell cycle regulatory CDK2/CDK4 protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing evidence points to BPA and its analogs as endocrine disrupting compounds that may inhibit biosynthesis, thereby affecting the male gonad development and maturation and eventually leading to TDS 2,4,27 . This research aimed to explore the effect of TMBPA (a BPA analog) on FLC function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations